A Closer Look at Lombok Tour Guides - Marham Jupri Hadi; Ulil Azmi; Lume; Tarmizi (Fakultas Sastra Universitas Nahdlatul Wathan Mataram, 2021)
Research on tourism suggests that tourist guides are key representatives in the tourism industry as they contribute significantly to the satisfaction of visitors and affect whether or not the tourist will revisit destinations. The present article reviews the existing literature on tourist guides from diverse perspectives in the hope that it would shed light on this career brighter. It begins with the definition of tourist guides, their key roles in the tourism industry, future of tourist guides, education and training and their needs for further learning. This paper also provide a recommendation on the materials to include for a tour guide training, particularly in Lombok.